Biomarkers of extracellular matrix turnover are associated with emphysema and eosinophilic-bronchitis in COPD. Issue 1 (December 2017) - Bihlet, Asger; Karsdal, Morten; Sand, Jannie; Leeming, Diana; Roberts, Mustimbo; White, Wendy; Bowler, Russell
Abstract Background Chronic obstructive pulmonary disease (COPD) is characterized by airflow obstruction and loss of lung tissue mainly consisting of extracellular matrix (ECM). Three of the main ECM components are type I collagen, the main constituent in the interstitial matrix, type VI collagen, and elastin, the signature protein of the lungs. During pathological remodeling driven by inflammatory cells and proteases, fragments of these proteins are released into the bloodstream, where they may serve as biomarkers for disease phenotypes. The aim of this study was to investigate the lung ECM remodeling in healthy controls and COPD patients in the COPDGene study. Methods The COPDGene study recruited 10, 300 COPD patients in 21 centers. A subset of 89 patients from one site (National Jewish Health), including 52 COPD patients, 12 never-smoker controls and 25 smokers without COPD controls, were studied for serum ECM biomarkers reflecting inflammation-driven type I and VI collagen breakdown (C1M and C6M, respectively), type VI collagen formation (Pro-C6), as well as elastin breakdown mediated by neutrophil elastase (EL-NE). Correlation of biomarkers with lung function, the SF-36 quality of life questionnaire, and other clinical characteristics was also performed. Results The circulating concentrations of biomarkers C6M, Pro-C6, and EL-NE were significantly elevated in COPD patients compared to never-smoking control patients (allp < 0.05). EL-NE was significantly elevated in emphysema patients compared to smoking controls (p < 0.05) and never-smoking controls (p < 0.005), by more than 250%. C1M was inversely associated with forced expiratory volume in 1 s (FEV1 ) (r = −0.344, p = 0.001), as was EL-NE (r = −0.302, p = 0.004) and Pro-C6 (r = −0.259, p = 0.015). In the patients with COPD, Pro-C6 was correlated with percent predicted Forced Vital Capacity (FVC) (r = 0.281, p = 0.046) and quality of life using SF-36. C6M and Pro-C6, were positively correlated with blood eosinophil numbers in COPD patients (r = 0.382, p = 0.006 andr = 0.351, p = 0.012, respectively). Conclusions These data suggest that type VI collagen turnover and elastin degradation by neutrophil elastase are associated with COPD-induced inflammation (eosinophil-bronchitis) and emphysema. Serological assessment of type VI collagen and elastin turnover may assist in identification of phenotypes likely to be associated with progression and amenable to precision medicine for clinical trials.